Odpowiedź:
Szczegółowe wyjaśnienie:
2.
a)
9x =4x +2 |-4x
9x-4x = 4x+2-4x
5x=2 |:5
x = 2/5
b)
2x = 8-6x |+6x
2x+6x = 8-6x+6x
8x = 8 | :8
x = 1
c)
4(x+7) = -6
4x + 28 = -6 | -28
4x +28 - 28= -6 - 28
4x = -34 | :4
x = -34/4
d)
7x = 8 -(x+6)
7x = 8 - x -6 | +x
7x + x = 8 -x - 6 +x
8x = 2 | :8
x = 2/8
e)
(x-7)/3 = 4 | *3
3 *(x-7)/3 = 4*3
x-7 = 12 | +7
x -7 + 7 = 12 + 7
x = 19
3.
a)
4x + 5 = 2x - 3 |-5
4x + 5 - 5 = 2x - 3 - 5
4x = 2x - 8 |- 2x
4x - 2x = 2x -8 -2x
2x = -8 | :2
x = -4
b)
4x - 8 = 6 - 3x | +8
4x - 8 + 8 = 6 - 3x + 8
4x = -3x +14 | +3x
4x + 3x = -3x + 14 + 3x
7x = 14 | : 7
x = 2